Tourism competitiveness: a cluster based approach for the sri lanka - Fernando, I.N. (university of Jaffna, 2014)
Tourism has regarded as one of the fastest growing service industries and a main source of foreign income for many economies and further, by the vast human potential, national materials and through multiple effects on areas of references, tourism acts as a stimulating factor for economic development. Tourism has inherited its nature by bonding people with leisure activities, that allows to inspire nature, destinations and own lives with traveling and culture of other nations. The objective of this paper is to identify the elements of a new paradigm that would help to become a competitive tourism destination within global tourism market for Sri Lankan Tourism cluster. Primary data has collected by administering an integrated model developed and number of respondents is 431 from two tourism clusters, Sea and Sand and Nature based cluster. Descriptive statistics have administered through hypotheses testing for the both clusters. Results revealed that innovation focus is weaker as in availability of packages in experience innovations, process innovations, autonomy given by organization to workforce on innovations, proactive towards innovativeness and workforce training by organization and country level innovations. The strategies have proposed for the sector development.
Keywords: Cluster; Competitiveness; Innovation focus; Tourism